Accessing local support online: Mothers' experiences of local Breastfeeding Support Facebook groups - Holly Morse; Amy Brown (Wiley, 2021)
Abstract The importance of support to breastfeeding success is well established, as are the difficulties many mothers face in accessing the support they need. With the majority of UK mothers now accessing social media for support, Breastfeeding Support Facebook (BSF) groups have increased exponentially. BSF groups vary in type (local or national/international) and in moderation-overseen by breastfeeding mothers and by midwives or trained lactation specialists. Some groups aimed at supporting mothers in a specific geographical area also have associated face‐to‐face groups, facilitated as either professional or peer support. Little is currently known about these specific local groups, their prevalence, impact or value to mothers. This paper examines mothers' experiences of using local BSF groups and why they value them as part of a larger study exploring the impact of midwife moderation on these groups. An online survey consisting of open and closed questions was completed by 2028 mothers. Findings identified that local BSF groups are widely used and highly valued for their connection with local face‐to‐face services and other mothers. They offer access to expertise and shared experience in a format mothers find convenient and timely, improving confidence and self‐efficacy. Local BSF groups enable the formation of support networks and development of breastfeeding knowledge that mothers credit with increased well‐being, motivation and breastfeeding duration. As such, they have the potential to add value to local face‐to‐face services and improve breastfeeding experiences and knowledge in communities. The findings have important implications to support the development of integrated online interventions to improve public health.